To solve the equation, you can start by distributed the 1.26 to the terms inside the parentheses:
1.26(x) - 1.26(7.352) = 6.426
Next, multiply 1.26 by 7.352:
1.26x - 9.264 = 6.426
Now, add 9.264 to both sides of the equation:
1.26x = 6.426 + 9.264
Combine the terms on the right side:
1.26x = 15.69
Finally, divide both sides of the equation by 1.26:
x = 15.69 / 1.26
Simplifying the division:
x ≈ 12.429
Therefore, the solution to the equation 1.26(x-7.352) = 6.426 is x ≈ 12.429.
what is the solution to the equation 1.26 (x-7.352) = 6.426 when solving for x?
1 answer